Anthropogenic hyperactivity for natural resources increases heavy metals concentrations in the environment: Toxicity of healthy food and cancer risks estimated - David Johane Machate (Journal of Trace Elements and Minerals, 2023)
Anthropogenic hyperactivities for natural resources cause increasing concentrations of heavy metals and metalloids in the environment, which hazard human health. This review highlights high concentration of heavy metals and metalloids in principal food daily intake and nutritionally accepted as healthy products, which were correlated with production sites, plus carcinogenic risks calculated and some metabolic diseases associated with reported cancer risk. Heavy metals (Al, Pb, Cu, Zn, Cd, Hg, Cr, Ni, Mn, Fe, Co) and metalloids (As, Se) are increasing in arable soil, aquatic and air environment affecting the food chain security and human health. Minimum and maximum heavy metals concentrations in foodstuffs calculated in mg kg–1 to Pb (0.0017 – 30.5); Cu (0.008 – 140.15); Cr (0.01 – 35.89); As (0.002 – 50.34); Zn (2.23 – 229.14); Cd (0.003 – 50.9); Ni (0.02 – 92.1); Fe (0.02 – 654.65); Mn (0.04 – 373.38); Hg (0.002 – 3.51); Co (0.01 – 5.1); Al (2.3 – 349) and Se (0.6 – 1.3). Maximum values were above of permissible limits by FAO/WHO. Minimum values to As and Pb: carbohydrates > vegetables and fruits > fish and seafood > meat, Cr (vegetables and fruits > carbohydrates > fish and seafood > meat), Cd (vegetables and fruits = meat > carbohydrates > fish), whereas Ni (carbohydrates > meat > fish and seafood > vegetables and fruits. Maximum values to As: vegetables and fruits > carbohydrates > fish and seafood > meat, Cr (meat > fish and seafood > vegetables and fruits > carbohydrates), Pb (carbohydrates > fish and seafood > vegetables and fruits > meat), Cd (meat > fish and seafood > carbohydrates > vegetables and fruits), while Ni (vegetables and fruits > meat > carbohydrates > fish and seafood). Heavy metals concentrations in foodstuffs are higher than cancer risk (CR > 10–4), hazard quotient and hazard index (HQ and HI > 1), demonstrating the major possible occurrence of cancer for the consumers aged 1 to ≥ 30 years old during the living time. This review paves the way for discussion of national and international financial support on mapping heavy metals in several healthy foodstuffs.